2015
DOI: 10.1108/caer-09-2012-0100
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting farmers’ participation in China’s group guarantee lending program

Abstract: Purpose – Based on a survey of 897 farm households, the purpose of this paper is to build a framework using cluster analysis to explain how farmers make decisions on joining group guarantee, and analyzes factors influencing their decisions using multinomial and binary Logit regressions. Design/methodology/approach – The approach of combining cluster analysis with Logit regression is an innovative approach to survey assessment. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
3
17
1
Order By: Relevance
“…This is indicative that rural agriculture still serves as a major source of employment for the teeming youth in China. This finding is in contrast with that of Kong et al (2015), who found that many rural areas in China have been deserted by the youth due to rural-urban migration. This finding, therefore, implies that farmer entrepreneurship can help reduce youth unemployment.…”
Section: Resultscontrasting
confidence: 91%
“…This is indicative that rural agriculture still serves as a major source of employment for the teeming youth in China. This finding is in contrast with that of Kong et al (2015), who found that many rural areas in China have been deserted by the youth due to rural-urban migration. This finding, therefore, implies that farmer entrepreneurship can help reduce youth unemployment.…”
Section: Resultscontrasting
confidence: 91%
“…Although the evidence that risk rationing among Chinese farmers is low (Verteramo-Chiu et al, 2014), these results indicate that the demand for collateral or guaranteed loans will be lower than credit loans. This is consistent with the findings of Kong et al (2015). We can infer that the demand for credit loans will be more elastic than the demand for collateral or guarantee loans.…”
Section: Institutionsupporting
confidence: 91%
“…Policies put in place by lenders to address risk and asymmetric information can also have demand side effects. Kong et al (2015) investigated the group guarantee and found that, generally, farmers did not form group guarantees voluntarily but were required to do so by the lender. Older farmers were less likely to borrow under a group guarantee or voluntarily join a group guarantee as guarantor; guarantors in a group guarantee are more likely to be risk takers or not too risk adverse; farmers who mistrust lenders are less likely to join a group guarantee.…”
Section: Attributes and Levels Identificationmentioning
confidence: 99%
“…Generally, the main microcredit attributes that have been used to explain the preferences of poor households are interest rate, repayment schedule, loan size and collateral method (Boucher et al, 2008;Tsukada et al, 2010;Sagamba et al, 2013;Kong et al, 2015). Interest rate, which is the price of financial service, has received the most attention ( Janvry et al, 2010;Rashid et al, 2011;Khandker and Koolwal, 2016;Tan and Lin, 2016).…”
Section: Introductionmentioning
confidence: 99%